Spiritual and pedagogical aspects of the patient’s relationship with people supporting him/her - Mastalski, Janusz (Psychoonkologia, 2018)
The problem of building appropriate relationships between a patient and persons supporting him/her is an important element in the treatment process. In these relationships the pedagogical and spiritual aspect is of particular importance. The most important categories on which these relationships are built include: the meaning of life, time, forgiveness, love, transcendence, needs, quality of being and perspectives. All these categories can be considered from spiritual and educational sides. They have a significant impact on the psychophysical condition of both the patient and those who support him/her. It seems that one of the most difficult issues concerning stress between illness and health is loneliness. Often it is so penetrating that it is hard to hold in a weakened psyche and in the spiritual sphere as well. Loneliness is an obstacle to the creative experience of illness (cancer as well), which does not always have to lead to loss of life. These threats specifically indicate the need to appreciate the spiritual elements in health promotion. Among them are: a crystallised meaning of life; a coherent system of values; faith; regular meeting of the Sacrum (prayer) and the religious approach to another. The anthropological premise suggests that a person has to develop integrally to maintain specific physical, mental, spiritual, and social balance. There is a huge need for health promotion, in which an important component is the spiritual sphere.